Economic Management of Late Blight (Phytophthora infestans L.) of Potato in Eastern Tarai of Nepal - Chaurasia, Prem CP (Nepal Agriculture Research Journal, 2010)
Field experiments were carried out at Regional Agriculture Research Station, Tarahara in three consecutive years (1997-2000) during winter season to know the economic sprays of different fungicides to manage late blight disease of potato. Late blight susceptible cultivar of potato Kufri Sindhuri was used for the experiment. Krinoxyl gold (metalaxyl 8% and mancozeb 64%) at the rate of 1.5 g/l, Dithane M- 45 (mancozeb 75%) @ 0.3% and Bordeaux mixture @ 10 g copper sulfate and 10 g lime/l of water and their different combinations were tested in randomized complete block design with three replications. Terminal disease severity was the highest (7.9) on 0-9 scale disease rating in unsprayed check and it was significantly higher than those of other fungicides sprays. Plots with three sprays of Dithane M- 45 @ 0.3% recorded the lowest (2.4) terminal disease severity. Disease development was the fastest in the unsprayed plot compared to all other treatments. Similarly apparent infection rate was the highest in unsprayed treatment. Area Under the Disease Progress Curve was also the highest in unsprayed plot and it was significantly higher than those of other treatments. Tuber yield was the lowest (3.93 kg/4.5 m2 plot in unsprayed and the highest (6.08 kg), in the plot receiving four sprays of Dithane M-45 @ 0.3 % and this was at par with the tuber yield of plots receiving two and three sprays of Dithane M-45. Benefit cost ratio was the highest (1.54) in case of two sprays of Dithane M-45 @ 0.3% at 10 days intervals. All others fungicide spays were uneconomical under Eastern Tarai condition. Key words: Eastern Tarai; economic spray; Dithane M-45; late blight management; potato DOI: 10.3126/narj.v6i0.3365 Nepal Agriculture Research Journal Vol.6 2005 pp.57-61